Faunistic studies of odonates (insecta: odonata) in Johor, Peninsular Malaysia - Abdul Aziz, Muhamad Amirul Ashraf; Mohamed, Maryati; Tokiman, Lili (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
The purpose of this research is to study the diversity and distribution of odonates in Johor, Peninsular Malaysia. The method used for odonate sampling was manual collection along 1 km line transect using aerial net. Overall, a total of 2222 individuals under 84 species from 13 families and 58 genera were recorded. Family Libellulidae was the most well-represented family. Shannon Diversity Index (H’) and Evenness Index (E) were highest in Endau-Rompin Johor National Park (H’= 3.155; E= 0.733) and lowest in Soga Perdana Recreational Forest (H’= 2.444; E= 0.501). To determine the site with highest conservation priority, the ecological data and entomotourism criteria was further analyzed using grid analysis. The site with highest priority was Endau-Rompin Johor National Park with a score value of 52 while the lowest priority was recorded in Sungai Sayong with a score value of 35. All these data will be helpful in assisting towards a better management of the conservation areas in Johor.